Religion and Revolution Spiritual and Political Islam in Ernesto Cardenal. - Morrow, John Andrew (Newcastle upon Tyne : Cambridge Scholars Pub., 2012)
Religion and Revolution provides a comprehensive study of spiritual and political Islam in Ernesto Cardenal, the great Latin American poet, priest, and revolutionary. The work studies the relationship between Thomas Merton and?ufism, Cardenal's connection to spiritual Islam, as well as the?ufi sources cited in his Cosmic Canticle. The work equally examines the impact of political Islam on his ideology, focusing particularly on his trip to Iran during the very triumph of the Islamic Revoluti ...
TABLE OF CONTENTS; FOREWORD; PREFACE; ACKNOWLEDGEMENTS; TRANSLITERATION; INTRODUCTION; CHAPTER ONE; CHAPTER TWO; CHAPTER THREE; CHAPTER FOUR; CHAPTER FIVE; CHAPTER SIX; CHAPTER SEVEN; CHAPTER EIGHT; CHAPTER NINE; CHAPTER TEN; CHAPTER ELEVEN; CONCLUSIONS; WORKS CITED; INTERLUDE OF THE REVOLUTION IN IRAN; ERNESTO CARDENAL IN IRAN; INDEX.
Description based on print version record.
Keywords: Cardenal, Ernesto -- Criticism and interpretation; Cardenal, Ernesto -- Themes, motives; Cardenal, Ernesto -- Translations; Cardenal, Ernesto -- Criticism and interpretation; Cardenal, Ernesto -- Themes, motives; Islam in literature; RELIGION / Islam / Theology; Electronic books